An exploration of the destructive impact of the construct of physical beauty on the African American woman. An analysis of Toni Morrison: The bluest eye (1970) and Zora Neale Hurston: Their eyes were watching God (1937) - Zimunya, Charntel Chiedza (Midlands State University, 2017)
The crux of the study is to unearth the effects of the process of the construct of physical beauty on the Black American woman. The study also analyses the inferiority, color complex which is defined as the psychological fixation about color and feature that leads to whites discriminating the blacks. It is in the study that I also ask how issues of the constructs of physical beauty by the African American woman leads to issues of continued self –denial, denial by the superior race and identity crisis. Throughout the history of colonialism and slavery the black race or the black colour so to speak has always been associated with negative stereotypes such as barbaric, evil and ugly. Such stereotypes have forever burdened the black woman especially the fact of ugliness. As such the study seeks to reveal how the black woman tries to run away from these stereotypes imposed on them by the coloniser, the master or the white woman who refer to themselves as the complete opposite who are clean and above all beautiful. The Black woman, through exposure and pressure from their immediate community, have put much great efforts to become white that is to become beautiful that is to have blue eyes and long blond hair as is revealed by Morrison and Hurston’s work. However these efforts are fruitless in fact affected the black woman that is to imply that they have become a taste of their own medicine. The have contributed more to on-going self-denial, identity crisis and continuous denial by those whom they try to imitate as they ultimately realise that they will never operate on the same footage with them.